DIPLOMASI INDONESIA TERHADAP MALAYSIA DALAM MENGIMPLEMENTASIKAN PROYEK KERJASAMA INDONESIA- MALAYSIA-THAILAND GROWTH TRIANGLE (IMT-GT) PERIODE 2012-2017 : Studi Kasus Proyek Ro-Ro Dumai - Malaka - Trias Rizkia Pertiwi, - (2018)
This research discusses about diplomacy Indonesia against Malaysia in the IMT- GT cooperation to implement the project of Ro-Ro Dumai - Malacca period 2012- 2017. This research uses descriptive method with an effort to try to explain what Indonesia has been doing so that project Ro-Ro Dumai-Malacca can be implemented. This research uses theories of diplomacy, national interest and the concept of cooperation of the sub-regional (growth-triangle) as well as data collection techniques using primary data obtained through interviews while secondary data obtained through books, journals, and internet sites. In conclusion, in the year 2017 has been agreed upon by the Minister of Transportation of the two countries that the project Ro-Ro Damai-Malacca will soon be implemented in the year 2019